1982
DOI: 10.1079/bjn19820136
|View full text |Cite
|
Sign up to set email alerts
|

The flow of endogenous nitrogen in the digestive tract of young pigs

Abstract: There are a number of individual components which can be added to make the total endogenous nitrogen flow. Corring (1975) found that pancreatic secretions amounted to 3-4 g N/d for the 45 kg pig or 11 7; of the dietary N intake. Horszczaruk et al. (1974) estimated from studies with isolated loops ofjejunum that the total endogenous N secretions in the intestines could be 1CL22 g/d.Zebrowska et al. (1975) fitted 50 kg pigs with re-entrant cannulas in the duodenum and ileum and estimated endogenous N secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
4
14
0
1
Order By: Relevance
“…However, in a recent literature review, the same authors [10] suggested that ENL are higher in young pigs and that the BW effect decreases rapidly as BW increases. This hypothesis is supported by data of ENL obtained on young animals: piglets weighing less than 10 kg and fed a N-free diet excrete from 3.5 to 4.6 g endogenous N·kg -1 DMI [11,12] whereas the average value for pigs weighing from 30 to 100 kg reaches only 1.7 g N·kg -1 DMI [13]. Apart of these higher ENL in piglets can be ascribed to a lower DMI.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, in a recent literature review, the same authors [10] suggested that ENL are higher in young pigs and that the BW effect decreases rapidly as BW increases. This hypothesis is supported by data of ENL obtained on young animals: piglets weighing less than 10 kg and fed a N-free diet excrete from 3.5 to 4.6 g endogenous N·kg -1 DMI [11,12] whereas the average value for pigs weighing from 30 to 100 kg reaches only 1.7 g N·kg -1 DMI [13]. Apart of these higher ENL in piglets can be ascribed to a lower DMI.…”
Section: Introductionsupporting
confidence: 70%
“…Leibholz [11] and Wilson and Leibholz [12] fed young pigs (27 to 35-d old) a N-free diet and measured ileal ENL ranging from 3.5 to 4.6 g N·kg -1 DMI. However, the DMI was low (45 g DM·kg -1 BW 0.75 ·day).…”
Section: Discussionmentioning
confidence: 99%
“…Leibholz (1982) found similar values for ileal ENL when either a casein-containing diet or a protein-free diet was fed to growing pigs (3.4 vs. 3.0 g kg -1 DMI, respectively). Fuller and Cadenhead (1991), on the other hand, observed lower ileal ENL in pigs fed a protein-free diet with added casein and crystalline amino acids as compared to pigs fed just the protein-free diet (4.3 vs 5.8 g d -1 , respectively).…”
Section: Ii41 Conventional Methods: Feeding Protein-free Diets Fementioning
confidence: 49%
“…Since the amount of dietary protein could also affect the endogenous nitrogen losses, the regression method also is not very accurate in determining endogenous nitrogen losses in animals fed protein-containing diets. Leibholz (1982) studied the endogenous nitrogen secretion in young pigs (4 weeks of age). She used the regression method to assess endogenous N losses with a feed based on milk protein.…”
Section: Discussionmentioning
confidence: 99%